How Eco-Conscious Choices are Shaping Generation Z’S Tumbler Market - Rahmawati, Dwi (Commercium : Journal of Business and Management, 2024)
This study reveals how consumer and environmental trends are affecting Indonesia's tumbler market, emphasizing the eco-conscious habits of Generation Z. Environmental issues including pollution, deforestation, and climate change have made sustainable materials and methods even more important. As much as 105 Gen Z taken a role as a respondent in this study, by filled out a set of a questionnaire. As a result of product improvements that meet Gen Z's need for sustainability, the Indonesian tumbler industry has grown quite significantly. The study used a quantitative technique to examine how the marketing mix—which includes product, price, site, and promotion—affects the Generation Z’s purchasing decisions of, who were primarily university students in various provinces in Indonesia. The results show that while price and location have less impact on purchasing decisions, product characteristics and advertising tactics do. Regression analysis supports the model's prediction power, while validity and reliability tests validate the power of measuring instruments. This study sheds light on how important strategic marketing is to attract eco-conscious customers and offers guidance to companies adjusting to Indonesia's growing green consumer culture.